RANCANG BANGUN APLIKASI KAMUS BAHASA MBOJO BERBASIS ANDROID - Ryan Suarantalla; Yuliadi Idrus; Erwin Martadinata; Furdi Adrisah (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Mbojo language is one of the regional languages ??that has different characteristics from other languages, both in the fields of phonology, morphology, syntax and other fields. This study aims to convert Mbojo language dictionary data which is still in the form of a book into digital form, make it easier for the indigenous people of the Bima and Dompu area or people outside the Bima and Dompu area to be able to interact, and preserve the regional language of Bima and Dompu which is a cultural heritage. This study used the prototype software development method and was built using Ionic 3 and the Firebase database. The data collection method uses literature study techniques with data sources from the Mbojo Indonesian Language Dictionary book, Language Development and Development Agency for the Province of NTB, Ministry of Education and Culture 2015 and uses the black box testing method, namely testing carried out by testing the software in terms of functionality. The results of the study are the Android-Based Mbojo Language Dictionary Application which can be accessed through the Play Store equipped with a dictionary including vocabulary search, learning, introduction to the dictionary, and about the application.